Pharmacognostical Evaluation and Comparative Phytochemical Screening of Rumex vesicarius L. - Ramesh L londonkar; Asha Tukappa N.K (International Journal of Phytomedicine, 2013)
Pharmacognosy is a simple and reliable tool by which complete information of the crude drug can be obtained. Therefore in this context the detailed pharmacognostic study of various parts like leaf, stem, and root of Rumex vesicarius L. has been carried out with the aim to establish its pharmacognostical standards. The parameters selected were physicochemical, fluorescence analysis and preliminary phytochemical screening along with mineral analysis. In physico-chemical evaluation the ash values and extractive values were studied.. The powder of Rumex vesicarius.L was successively extracted with petroleum ether, chloroform, methanol and water by both cold maceration and hot soxhlet extraction for the identification of the best solvent and method. Preliminary phytochemical screening was carried out for all the extracts. Fluorescence analysis performed showed the wide range of fluorescence colours for the crude powder. The preliminary phytochemical screening shows maximum chemical constituents in the different extract obtained from cold maceration of different plant parts compared to extract obtained from hot soxhlet extraction. The principal constituents of Rumex vesicarius L. include phenols, tannins, flavonoids, saponins, triterpenoids, alkaloids, anthraquinones, quinines, reducing sugars, proteins, lipids and carbohydrates. The inorganic elementary analysis performed revealed the presence of sodium, chloride and iron. The present study indicates the pharmacognostical and physicochemical characteristics and preliminary properties of the different parts of Rumex vesicarius.L for the identification of the drug in the dry form. Thus plays a crucial role in standardization of crude drug.